2002
DOI: 10.1002/1099-0690(200203)2002:6<1063::aid-ejoc1063>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of 5,6-Disubstituted 3-Methyl-2(2H)-pyranones and 6-Substituted 3-Methyl-2(2H)-pyranones, Including Fusalanipyrone and Gibepyrone A

Abstract: The 6-substituted 3-bromo-5-iodo-2(2H)-pyranones 11, prepared by iodolactonization of the corresponding 5-substituted (E)-2-bromo-2-en-4-ynoic acids 10, were used as precursors to 5,6-disubstituted 3-methyl-2(2H)-pyranones 8 and 6-substituted 3-methyl-2(2H)-pyranones 7. The synthesis of compounds 8 involved two consecutive Stille-type reactions, whereas the approach followed to prepare compounds 7 consisted of the selective reduction of the dihalogen derivatives 11 to the corresponding 6-substituted 3-bromo-2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…38) Consequently, the geometric configuration of the 2-butenyl group in nocapyrone H (1) was consistent with the E-configuration. Thus, the structure of 1 was determined to be (E)-6-(but-2-en-2-yl)-3-isobutyl-2H-pyran-2-one.…”
Section: Resultsmentioning
confidence: 99%
“…38) Consequently, the geometric configuration of the 2-butenyl group in nocapyrone H (1) was consistent with the E-configuration. Thus, the structure of 1 was determined to be (E)-6-(but-2-en-2-yl)-3-isobutyl-2H-pyran-2-one.…”
Section: Resultsmentioning
confidence: 99%
“…1) supported the suggestion that the 2-buten-2-yl and isobutyl residues were linked to C-6 and C-3 of the 2-pyrone nucleus, respectively. 17,18 This deduction was conrmed from a NOE difference experiment. 13,16 By contrast, a related compound, fusalanipyrone with a Z-conguration, showed downeld shi of H 3 C-10 (d C 21.5).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that alcohols led to trans products in low selectivity, while ethers and silylethers produced cis isomers in excellent selectivity ( Table 2). A possible explanation for this high selectivity is the greater stability (due to the lack of vicinal interaction) of the oxonium ion intermediate (12) compared to (13) and (14), where R 1 is a bulk group (in the case of ethers and silylethers).…”
Section: Intramolecular Coiodination Of Alkenols and Unsaturated Ethementioning
confidence: 99%